Antidepressant activity of Spathodea campanulata in mice and predictive affinity of spatheosides towards type A monoamine oxidase - Bajaj, Jitendra; Dwivedi, Jaya; Sahu, Ram; Dave, Vivek; Verma, Kanika; Joshi, Sushil; Sati, Bhawana; Sharma, Swapnil; Seidel, Veronique; Mishra, Abhay Prakash (Cellular and Molecular Biology, 2021)
The antidepressant activity of Spathodea campanulata flowers was evaluated in mice and in silico. When tested at doses of 200 and 400 mg/kg, the methanol extract of S. campanulata (MESC) showed dose-dependent antidepressant activity in the force swim test (FST), tail suspension test (TST), lithium chloride-induced twitches test and the open field test. In FST and TST, animals treated with MESC demonstrated a significant decrease in the immobility period compared to the control group. The lithium chloride-induced head twitches were significantly reduced following administration of MESC. The latter, at the dose of 400 mg/kg, also significantly reduced locomotor activity. Following administration of MESC, changes in the levels of serum corticosterone, and of norepinephrine, dopamine, serotonin, 4-hydroxy-3-methoxyphenylglycol (MHPG), 4-dihydroxyphenylacetic acid (DOPAC), and 5-hydroxyindoleacetic acid (5-HIAA) were measured in different brain regions using HPLC. The presence of spatheoside A (m/z 541) and spatheoside B (m/z 559) in MESC was detected using HPLC/ESI-MS. These two iridoids demonstrated a high predictive binding affinity for the active site of the type A monoamine oxidase (MAO-A) enzyme with scores of 99.40 and 93.54, respectively.  These data suggest that S. campanulata flowers warrants further investigation as a source of novel templates for antidepressive drugs.